Implementasi Program Corporate Social Responbility (CSR) Program Penghijauan PT Selecta dalam Mempertahankan Citra Perusahaan - Harnadi, Alfianta Dwi; Cikusin, Yaqub; Ahmadi, Rulam (Universitas Nahdlatul Ulama Blitar, 2024)
PT Selecta is a PT (Limited Liability Company) based company with a unique work culture. The aim of this research is to find out how it is implemented, what roles the actors play, and what the public's perception is. This examination uses a subjective methodology with an illustrative exploration type. PT Selecta is the location for this research. Interviews, observations, and document research are the methods used in this research to collect data. The results of the research show that the steps for implementing PT Selecta's corporate social responsibility program to prevent environmental pollution due to the company's production activities to the Gondang community and maintain the company's image include the planning stage and this shows that several implementation stages have been completed, including the preparation stage, implementation stage, observation and evaluation stage. The duties of partners include the duties of public authorities who are ready to evaluate the methods implemented by PT Selecta, as well as the duties of a secret kingdom which does not guarantee that the organizations formed by various parties will last forever. Willing to take part in all PT Selecta CSR program activities and play a role in protecting community trees. The community appreciates PT Selecta's environmentally friendly CSR program if it has legitimate goals and is beneficial to the community. The results of the implementation are very positive and the community has the impression that the company pays attention to the community.